Novel drug delivery approaches on antiviral and antiretroviral agents - Pooja Sharma; Anuj Chawla; Sandeep Arora; Pravin Pawar (Wolters Kluwer Medknow Publications, 2012)
Viruses have the property to replicate very fast in host cell. It can attack any part of host cell. Therefore, the clinical efficacy of antiviral drugs and its bioavailability is more important concern taken into account to treat viral infections. The oral and parenteral routes of drug administration have several shortcomings, however, which could lead to the search for formulating better delivery systems. Now, a day's novel drug delivery systems (NDDS) proved to be a better approach to enhance the effectiveness of the antivirals and improve the patient compliance and decrease the adverse effect. The NDDS have reduced the dosing frequency and shorten the duration of treatment, thus, which could lead the treatment more cost-effective. The development of NDDS for antiviral and antiretroviral therapy aims to deliver the drug devoid of toxicity, with high compatibility and biodegradability, targeting the drug to specific sites for viral infection and in some instances it also avoid the first pass metabolism effect. This article aims to discuss the usefulness of novel delivery approaches of antiviral agents such as niosomes, microspheres, microemulsions, nanoparticles that are used in the treatment of various Herpes viruses and in human immunodeficiency virus (HIV) infections.